Spectral narrowing in the resonance fluorescence of a driven V-type quantum emitter near a two-dimensional plasmonic nanostructure array - Spyridon G. Kosionis; Vassilios Yannopapas; Emmanuel Paspalakis (Results in Physics)
We investigate the incoherent resonance fluorescence spectrum emitted by a three-level V-type quantum emitter, under the influence of a two-dimensional plasmonic nanosphere array. The V-type quantum system is driven by a coherent electromagnetic field whilst quantum interference effects in the spontaneous emission due to the presence of the plasmonic nanostructure are accounted for. The characteristics of the incoherent resonance fluorescence spectrum are studied, for different sets of parameters, aiming at the specification of the conditions under which an outstanding spectral narrowing, or either, quenching effects are manifested.